2020
DOI: 10.3390/md18120640
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Molecules from Extreme Environments

Abstract: Marine organisms inhabiting extreme habitats are a promising reservoir of bioactive compounds for drug discovery. Extreme environments, i.e., polar and hot regions, deep sea, hydrothermal vents, marine areas of high pressure or high salinity, experience conditions close to the limit of life. In these marine ecosystems, “hot spots” of biodiversity, organisms have adopted a huge variety of strategies to cope with such harsh conditions, such as the production of bioactive molecules potentially valuable for biotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…LAB is considerably a group of extreme bacteria due to their survival capability at a very low pH (Mbye et al, 2020) stress implied that those organisms are equipped with supporting cellular machinery, including proteins or enzymes (Giordano, 2020). As an example, LAB is known to have a very efficient proton pump allowing the bacteria to maintain their intracellular pH under very low environmental pH (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…LAB is considerably a group of extreme bacteria due to their survival capability at a very low pH (Mbye et al, 2020) stress implied that those organisms are equipped with supporting cellular machinery, including proteins or enzymes (Giordano, 2020). As an example, LAB is known to have a very efficient proton pump allowing the bacteria to maintain their intracellular pH under very low environmental pH (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of silver nanoparticles (AgNPs) by the Gram-negative Pseudomonas strain, isolated from the Antarctic marine ciliate Euplotes focardii, and showing antimicrobial activities against Escherichia coli, Staphylococcus aureus, and Candida albicans was reported (John et al, 2020). Silver nanoparticles were obtained by incubation of Pseudomonas cultures with silver nitrate (AgNO 3 ), and after that antimicrobial activity was tested against 12 human pathogens by using disk diffusion method (DDM) giving promising results (John et al, 2020;Giordano, 2020).…”
Section: Compounds With Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…For example, a longer period of larval development has been observed for sponges in Antarctica [ 10 ], where they represent the major component of the Antarctic zoobenthos (counting about 400 species; [ 10 , 11 ]). Previous studies have shown that Antarctic sponges may produce bioactive compounds for possible human applications [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. This study aims to further explore the Antarctic region and to give an overview of sponge bioactivity from different sites, their chemical composition, and the mechanism of action of the active principles.…”
Section: Introductionmentioning
confidence: 99%